2021
DOI: 10.1186/s12889-021-11842-1
|View full text |Cite
|
Sign up to set email alerts
|

An inventory of national surveillance systems assessing physical activity, sedentary behaviour and sport participation of adults in the European Union

Abstract: Background Physical inactivity has been recognised as a global public health problem that requires concerted action. This calls for systematic physical activity (PA) surveillance as a mechanism for assessing the problem and evaluating the effectiveness of related policies. Because countries tend to design their policy measures based on national surveillance data, here we present an inventory of existing national surveillance systems on PA, sedentary behaviour (SB) and sport participation (SP) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…PAQs have been a mainstay of measurement in most non-communicable diseases surveillance systems and epidemiological studies; however, their use is not unified. For example, a recent study of national surveillance systems for physical activity, sedentary behavior, and sport participation in the European Union [ 15 ] found that the International Physical Activity Questionnaire (IPAQ), with its long and short forms (IPAQ-LF and IPAQ-SF; [ 16 ]), prevails in the European Union (EU). Globally, the Global Physical Activity Questionnaire (GPAQ) is used in more than 120 countries worldwide and is used in surveys conducted by the World Health Organization (WHO) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAQs have been a mainstay of measurement in most non-communicable diseases surveillance systems and epidemiological studies; however, their use is not unified. For example, a recent study of national surveillance systems for physical activity, sedentary behavior, and sport participation in the European Union [ 15 ] found that the International Physical Activity Questionnaire (IPAQ), with its long and short forms (IPAQ-LF and IPAQ-SF; [ 16 ]), prevails in the European Union (EU). Globally, the Global Physical Activity Questionnaire (GPAQ) is used in more than 120 countries worldwide and is used in surveys conducted by the World Health Organization (WHO) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Still, wide variety of other PAQs is used in the EU. For example, the EU Eurobarometer uses the adapted IPAQ-SF [ 19 ], the European Health Interview Survey (EHIS) uses its own PAQ [ 20 ], Nordic countries use the Nordic Physical Activity Questionnaire [ 21 ], and many member states have their own national questionnaires [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Italy, according to official OECD statistics (9), is ranked 25th (out of the 37 OECD member states in 2017) for the prevalence of overweight and obesity, with a worryingly high prevalence in childhood (10,11). The poor adherence of the Italian population to the Mediterranean Diet, as well as the high level of sedentary lifestyle (12,13), could both be among the main factors to explain the rise in the prevalence of obesity in Italy (14). According to the data reported by DaSilva et al (15), further confirmed by Vilarnau et al (16), many countries in the Mediterranean basin were drifting away from the Mediterranean dietary pattern.…”
Section: The Health and The Nutritional Situation In Italymentioning
confidence: 90%
“…First, all the measures of this study were self-reported. Although self-reports have been widely used for gaining insight into the physical activity levels of populations [51], they have limited validity [52] and issues of recall and response bias (e.g., social desirability, inaccurate memory) [53]. Second, despite efforts to ensure that the cohort was as representative as possible of people with SMI in the UK, it may be that there are differences between the cohort participants and the general SMI population.…”
Section: Limitationsmentioning
confidence: 99%